PENGARUH KONFLIK PEKERJAAN-KELUARGA TERHADAP TURNOVER INTENTION MELALUI MEDIASI KEPUASAN KERJA PADA HOKI BANK CABANG GATOT SUBROTO - Paramita, I Gusti Agung Mirtha; Subudi, Made (E-Jurnal Manajemen; Vol 6 No 12 (2017), 2017)
This research was conducted in Hockey Bank Branch Gatot Subroto. The purpose of this study was to exame the effect of work-family conflict on turnover intention through meditation of job satisfaction. The sample of this research is 46 respondents with saturated sampling method. In this study data collection is done by distributing questionnaires using Likert scale. Analysis technique used in this research is path analysis. Based on the results of the analysis it was found that work-family conflict had a positive effect on turnover intention. Work-family conflict has a negative effect on job satisfaction. Job satisfaction has a negative effect on turnover intention. The study also proved that the role of mediation of job satisfaction on the influence of family-work conflict on turnover intention. For the company should provide good needs for employees and pay attention to the assignment and also the time of completion of tasks in accordance with the portion, so that employees are not burdened by the pressure of time.